The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1109/tvcg.2009.57
|View full text |Cite
|
Sign up to set email alerts
|

Tiled++: An Enhanced Tiled Hi-Res Display Wall

Abstract: In recent years, high-resolution displays have become increasingly important to decision makers and scientists because large screens combined with a high pixel count facilitate content rich, simultaneous display of computer-generated imagery and high-definition video data from multiple sources. Tiled displays are attractive due to their extended screen real estate, scalability, and low cost. LCD panels are usually preferred over projectors because of their superior resolution. One of the drawbacks of LCD-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…We found that the benefit of perceiving finer details of the data set outweighs these slight optical confusions. A user study we conducted [12] showed that sharp transitions between different levels of resolution on a tiled wall do not cause as much confusion as mismatches in brightness and color between screens. The problem of discontinuities caused by monitor bezels requires deeper investigation in the context of human-computer interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the benefit of perceiving finer details of the data set outweighs these slight optical confusions. A user study we conducted [12] showed that sharp transitions between different levels of resolution on a tiled wall do not cause as much confusion as mismatches in brightness and color between screens. The problem of discontinuities caused by monitor bezels requires deeper investigation in the context of human-computer interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of discontinuities caused by monitor bezels requires deeper investigation in the context of human-computer interaction. Software [25] as well as hardware dependent solutions [12] have already been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Rear-projection systems are still being developed, and have advantages such as being compatible with direct touch manipulation across tiles (an interaction typically hindered by bezels). But the higher pixel density, currently around 100dpi, the easier setup, and higher display quality of LCD panels, has made them a popular approach, enabling display capacities up to about 200 megapixels [1,4,9,24,25,26,28]. Such display capacity enables the visualization of large images, but also the juxtaposition of multiple datasets in coordinated views for compare and contrast tasks [29].…”
Section: Related Workmentioning
confidence: 99%
“…Tiled++ [9] projects a low-resolution version of the hidden regions on the bezels themselves. However, this only provides users with some sort of coarse preview of hidden information.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation